Optimasi Komposisi Hidroksipropil Metilselulosa dan Etil Selulosa dalam Preparasi Hollow Microspheres Kaptopril - Irawan, Eka Deddy; Farkha, Fara Sukma; Ameliana, Lidya (Pustaka Kesehatan, 2024)
Hypertension is a condition while blood pressure is increasing. The normal value of blood pressure is <120/80 mmHg. One of the drugs used to reduce blood pressure is captopril. Captopril has a short half-time, so it requires repeated administration that allows fluctuations. To solve this shortcoming, an approach was carried out using a controlled delivery system, hollow microspheres. The purpose of this research is to optimize and determine the amount of Hydroxypropyl Methylcellulose (HPMC) and Ethyl Cellulose (EC) polymers that can produce the optimum formula. Optimization is done using the factorial design method. The response that will be observed in this research is the value of entrapment efficiency, buoyancy, and particle size. The optimum formula was obtained in the combination of HPMC and EC amounts in captopril hollow microspheres are 75 mg HPMC and 200 mg EC.